2011
DOI: 10.1172/jci45114
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 deficiency in T cells leads to the Th17-associated development of premalignant gastroduodenal lesions in mice

Abstract: While there is evidence that specific T cell populations can promote the growth of established tumors, instances where T cell activity causes neoplasms to arise de novo are infrequent. Here, we employed two conditional mutagenesis systems to delete the TGF-β signaling pathway component Smad4 in T cells and observed the spontaneous development of massive polyps within the gastroduodenal regions of mice. The epithelial lesions contained increased levels of transcripts encoding IL-11, IL-6, TGF-β, IL-1β, and TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 94 publications
2
58
0
Order By: Relevance
“…Smad4 mutation has been associated with cancers in human and mice (Hahn et al, 2011; Howe et al, 1998; Kim et al, 2006; Miyaki and Kuroki, 2003). The immune etiology is not entirely clear, although enhanced Th cell responses may contribute to cancer development (Hahn et al, 2011; Kim et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smad4 mutation has been associated with cancers in human and mice (Hahn et al, 2011; Howe et al, 1998; Kim et al, 2006; Miyaki and Kuroki, 2003). The immune etiology is not entirely clear, although enhanced Th cell responses may contribute to cancer development (Hahn et al, 2011; Kim et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, mice with T cell specific deletion of Smad4 are grossly normal without apparent T cell activation (Yang et al, 2008b). In addition, when these mice are on a specific genetic background, they spontaneously develop cancer but not autoimmunity (Hahn et al, 2011; Kim et al, 2006). Similarly, people with germ-line mutations of Smad4 predispose to familial juvenile polyposis and gastrointestinal cancers (Howe et al, 1998; Miyaki and Kuroki, 2003) but not autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in isolated murine T cells, JNK phosphorylation was inversely associated with Smad4 protein expression (data not shown). Previous studies have indicated that constitutive JNK activity may promote the malignancy of B and T cells (21,31), while mice with a Smad4 deletion were observed to spontaneously develop gastrointestinal cancer (32,33). The possibility that a Smad4 deletion may initiate pancreatic cancer in humans is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these murine models of gastric cancer arise from the germline heterozygous or T cell-specific deletion of Smad4 [13][14][15][16]. The epithelium-autonomous role of Smad4 in suppressing gastric cancer has not yet been clearly defined.…”
Section: Deletion Of Smad4 and Pten In Murine Lgr5mentioning
confidence: 99%